Gamification elements and its impact on students - Mohd Yushaa, Nur Syazwani; Syed Khuzzan Alhabshi, Sh Mazlina; Hanid, Mahanim (Universiti Utara Malaysia, 2021)
This study reviewed past research with regards to gamification and to propose a conceptual framework model by mapping the relationships between gamification elements and its impacts towards university students’ learning outcomes. This paper synthesized theextant literature on gamification elements by conducting a review of the literature on gamification in the context of students’ learning in higher education. This paper has highlighted the gamification elements i.e. composed by rewards, feedback, points, badges, leaderboards, levels, progress bar, challenges and avatar that shown to influence and positively affecting students’ learning experience in Higher Education Institutions (HEIs) especially in improving their level of motivation, aid in engagement, improving result and achievement as well as inducing positive learning attitude. Investigating the impact of gamification elements means understanding under what circumstances gamification can be implemented to stimulate positive student’s learning behaviour in HEIs thus maximizing the use of gamification as an innovative approach of a new educational technology tool in teaching and learning. The findings of this paper provide reference for practitioners in mechanism design to encourage full potential of theimplementation of gamification by manipulation of various element in gamification to support an interactive and conducive learning experience.